A Survey of Prevalence of Voice Problems in School Teachers of Mysuru, India - K, Yeshoda; T, Jayakumar (Journal of All India Institute of Speech and Hearing)
The study aimed to estimate the prevalence of voice problems in teachers with a minimum of 5 years of teaching experience using Survey method. 372 school teachers (327 females and 45 males) from 60 schools in the city and six taluks of Mysuru participated. A validated questionnaire was used and all participants completed the questionnaire individually. Analysis involved compiling the scores obtained from the questionnaires to determine the risk factors for developing a voice problem. In general the results revealed that voice problems are prevalent in teachers with a point prevalence rate of 8.6%. A few variables (locality and type of environment of the schools and hours of teaching) were found to have signi cant efects on the voice of the participants. Life styles issues combined with individualistic vocal habits cultivated over a period of time to carry out professional responsibilities could be speculated as the main cause for the prevalence of most voice problems. Such insights prove bene cial in formulating strategic the management options for teachers’ voice problems and also sensitization programs to prevent the incidence of voice problems in teachers